"Can the intrapartum ultrasonography reduce the legal liability in distocic labor and delivery?". (18th April 2018) - Malvasi, Antonio; Montanari Vergallo, Gianluca; Tinelli, Andrea; Marinelli, Enrico
Abstract: The authors emphasize the importance of performing an intrapartum ultrasonography in order to prevent maternal and neonatal complications but also physician legal liability. The main advantages of using this technique are: improvement of fetal head's malposition diagnosis; prevention of maternal and fetal complications of childbirth due to the use of forceps or vacuum extractor (VE); a more accurate planning of cesarean section; a proof of professional correctness.